2009
DOI: 10.1111/j.1365-2095.2009.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the digestibility and metabolizability of the major nutrients and energy of maize leaves and barnyard grass in grass carp (Ctenopharyngodon idella)

Abstract: In the uplands of northern Vietnam, culture of grass carp contributes significantly to income and household food security of Black Thai farmers. Maize is one of the most important upland crops and barnyard grass is the most important weed in the paddy rice fields. Thus, these are frequently used by small‐scale fish farmers as fish feed. An 8‐week feeding trial was conducted simultaneously in a recirculation and in a respirometric system to determine the digestibility and metabolizability of the nutrients of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Grass carp under traditional pond management showed a d 13 C signature around -25 %, which suggests that maize leaves and mixed weeds are a substantial feed fraction contribution to the assimilation into fish biomass even though about 70 % of palatable leaf material applied to the ponds had a d 13 C lower than -28 %. This suggests a higher utilization of maize leaves and mixed weeds which is in line with the findings of Dongmeza et al (2010) who reported fresh maize leaf material to be suitable as feed for grass carp while banana and cassava leaves contained high levels of antinutrients ) and were therefore assimilated to a lesser extent.…”
Section: Natural Food Resourcessupporting
confidence: 87%
“…Grass carp under traditional pond management showed a d 13 C signature around -25 %, which suggests that maize leaves and mixed weeds are a substantial feed fraction contribution to the assimilation into fish biomass even though about 70 % of palatable leaf material applied to the ponds had a d 13 C lower than -28 %. This suggests a higher utilization of maize leaves and mixed weeds which is in line with the findings of Dongmeza et al (2010) who reported fresh maize leaf material to be suitable as feed for grass carp while banana and cassava leaves contained high levels of antinutrients ) and were therefore assimilated to a lesser extent.…”
Section: Natural Food Resourcessupporting
confidence: 87%
“…In the present study, the fiber contents of all experimental diets were lower than the critical value indicated before. However, it is reasonable to suggest that especially the cell wall of the corn meal is not easily broken by the fish, which could thus not make better use of the cell contents (Li 1996;Dongmeza et al 2010). Cell wall composition of high fiber feed ingredients shows that they contain large amounts of arabino-xylans, pectic polysaccharides and some cellulose.…”
Section: Discussionmentioning
confidence: 97%
“…However, not all of the plant materials currently applied have been found to be suitable as feed for the grass carp. Some of the leaves and grasses applied in the study area showed a limited feed value ) and several feeds even turned out to have a negative impact on fish growth (Tuan et al 2007;Dongmeza 2009;Dongmeza et al 2010). Further, the feed base for the non-grass carp species in this pond system is rather limited.…”
Section: The Integrated Agriculture-aquaculture System Used By Black mentioning
confidence: 91%
“…Within the framework of the Uplands Program, feeding trials were carried out in aquaria and respirometry systems at the University of Hohenheim and in an aquarium system at the Hanoi University of Agriculture. In the experiments at the University of Hohenheim, grass carp were either fed a standard diet (control group), with the standard diet supplemented with dried cassava leaves or weed mixtures Mix of monocotyles and dicotyles usually collected from paddy fields and dykes (e.g., Alternathera sessili, Commelina nudiflora, Cyperus rotundus, Digitaria timorensis, Eclipta prostata, Kyllinga monocephala, Sagitaria sagitifolia, Sporobolus indicus, Urochloa reptans and Wedelia calendulacea) (Dongmeza 2009), with leaves from banana or bamboo (Dongmeza 2009), or with the leaves of maize or barnyard grass (Dongmeza et al 2010). In all these trials, the leaves and weeds used, with the exception of the maize leaves, came from the farmers in Yen Chau.…”
Section: Current and Potential Feed Resources For The Local Aquacultumentioning
confidence: 99%
See 1 more Smart Citation